Pengaruh Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Beban Operasional dan Pendapatan Operasional (BOPO) Terhadap Return on Asset (ROA) Pada PT Bank Pembangunan Daerah Kalimantan Periode 2018 - 2022 - Suhendra Suhendra; Ibnu Aswat (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (JEBMA), 2024)
Abstract: This study aims to determine the influence of CAR, NIM, and BOPO on PT Bank Pembangunan Daerah Kalimantan for the period 2018-2022. The population of this study is all Bank Pembangunan Daerah Kalimantan, which consists of 4 companies. The sampling technique used is purposive sampling, which means the sample is taken based on certain considerations. The consideration is that Bank Pembangunan Daerah Kalimantan has complete financial data for a period of 5 years, namely 2018-2022. The data analysis method in this study is multiple regression analysis using SPSS Version 29 software. Based on the results of hypothesis testing, it can be concluded that CAR does not have a positive influence on ROA partially. NIM partially has a positive and significant influence on ROA. Meanwhile, BOPO does not have a significant influence on ROA in PT Bank Pembangunan Daerah Kalimantan for the period 2018-2022. Keywords: BOPO, CAR, NIM, ROA